2009
DOI: 10.1063/1.3075565
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetically coupled patterned media

Abstract: Magnetostatic interactions in patterned media are responsible for increasing the switching field distribution and reducing the thermal stability. Micromagnetic simulations indicate that a reduced saturation magnetization (Ms) and increased anisotropy constant (Ku) lead to better thermal stability. However, writability will be a concern with this approach. Patterned media with an antiferromagnetically coupled (AFC) recording media structure is studied to obtain high thermal stability even with a larger Ms and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Switching field distribution (SFD) is an important parameter in magnetic recording. 28 The SFD affects the writing process and hence the magnetic recording performance. Therefore, it is essential to obtain an SFD as narrow as possible.…”
Section: Patterned Recording Mediamentioning
confidence: 99%
“…Switching field distribution (SFD) is an important parameter in magnetic recording. 28 The SFD affects the writing process and hence the magnetic recording performance. Therefore, it is essential to obtain an SFD as narrow as possible.…”
Section: Patterned Recording Mediamentioning
confidence: 99%
“…5 The significance of magnetostatic fields from neighboring bits had been illustrated in micromagnetic simulations which showed that a single magnetic entity is more stable than the entity in a patterned medium. 6 This increase in SFD poses a challenge in the synchronization of writing on the patterned islands for the recording system, as well as an increase in write-in-error due to variations in the writing field needed for each bit. [7][8][9] Exchange coupled recording media is one approach to improve writability and hence write-in errors as well.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Recently, antiferromagnetically coupled (AFC) patterned media technology has been proposed to minimize SFD. 9,10 In order to achieve antiferromagnetic coupling at remanence after patterning, it is a prerequisite that the exchange coupling field (H ex ) acting on the thinner layer be greater than its coercivity (H c ). However, there is a challenge with this particular criterion.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] One of the crucial challenges of BPM is the widening of the switching field distribution (SFD). [5][6][7][8][9] The write-in-error is highly influenced by the SFD, and therefore narrow SFDs within nano-patterned arrays are needed to record onto each individual bit reliably without disturbing the surrounding neighbors. [6][7][8][9][10] Recently, antiferromagnetically coupled (AFC) patterned media technology has been proposed to minimize SFD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation